2015
DOI: 10.1007/s11356-015-4928-2
|View full text |Cite
|
Sign up to set email alerts
|

PM10 and PM2.5 composition over the Central Black Sea: origin and seasonal variability

Abstract: Daily PM10 and PM2.5 samples were collected between April 2009 and July 2010 at a rural site (Sinop) situated on the coast of the Central Black Sea. The concentrations of PM10 and PM2.5 were 23.2 ± 16.7 and 9.8 ± 6.9 μg m(-3), respectively. Coarse and fine filters were analyzed for Cl(-), NO3(-), SO4(2-), C2O4(2-), PO4(3-), Na(+), NH4(+), K(+), Mg(2+), and Ca(2+) by using ion chromatography. Elemental and organic carbon content in bulk quartz filters were also analyzed. The highest PM2.5 contribution to PM10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
(86 reference statements)
0
7
0
6
Order By: Relevance
“…In addition, previous studies have reported a high correlation between PM 10 and PM 2.5 emissions in China and beyond [54,55,56]. It is also reported that the contribution of PM 2.5 to PM 10 in the Central Black Sea in summer was 54% [57]. As such, to some extent, the estimation of PM 10 reveals the concentration of PM 2.5 .…”
Section: Discussionmentioning
confidence: 85%
“…In addition, previous studies have reported a high correlation between PM 10 and PM 2.5 emissions in China and beyond [54,55,56]. It is also reported that the contribution of PM 2.5 to PM 10 in the Central Black Sea in summer was 54% [57]. As such, to some extent, the estimation of PM 10 reveals the concentration of PM 2.5 .…”
Section: Discussionmentioning
confidence: 85%
“…Droughts and intensive exploitation of pastures lead to a reduction in vegetation cover in large areas of arid zones in Asia and Africa and the removal of dust particles from them [2]. As a result of sand and dust storms, dust can rise high into the atmosphere and be carried over long distances, often moving across the oceans [14][15][16][17]. Each year, such storms carry into the oceans an average of half a billion tons of minerals and nutrients, which, coming from the atmosphere, can affect the primary production of the ocean, including its coastal regions.…”
Section: Introductionmentioning
confidence: 99%
“…Засухи и интенсивная эксплуатация пастбищ приводят к сокращению растительного покрова на значительных площадях аридных зон Азии и Африки и выносу с них пылевых частиц [2]. В результате песчаных и пылевых бурь пыль может подниматься высоко в атмосферу и разноситься на большие расстояния, часто перемещаясь через океаны [14][15][16][17]. Ежегодно такие бури переносят в океаны в среднем полмиллиарда тонн минералов и биогенных веществ, которые, поступая из атмосферы, могут оказывать влияние на первичную продукцию океана, включая и прибрежные его районы.…”
unclassified